1926
DOI: 10.1055/s-0028-1127579
|View full text |Cite
|
Sign up to set email alerts
|

Ueber das weibliche Sexualhormon, das Hormon des östrischen Zyklus (Menformon)1). IV. Einfluß auf den Stoffwechsel, Widerstandsvermögen gegen physikalische und andere Eingriffe2)

Abstract: Ueber das weibliche Sexualhormon, das Hormon des östrischen Zyklus (Menformon) '). IV.Einfluß auf den StoffwechseJ, Widerstandsvermögen gegen physikalische und andere Eingriffe 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1928
1928
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…While it is generally recognized that estrogens are without demonstrable effect upon the mean level of arterial blood pressure (8,9,10,11,14,15), evidence is accumulating to show that the effects of estrogen on the peripheral circulation are quite widespread throughout the body, and are of a definite character. The following facts indicate this: the injection of estrogen causes swelling and changes in the water content of the sex-skin in certain primates (12); estrogen causes engorgement of the vessels in the nasal mucosa, including that of women (13); the injection of estrogen in the human is followed by a fall in capillary pressure and dilatation of the nail-bed capillary vessels (14); estrogen causes a decrease of venous pressure in the hand (15); and, finally, estrogen causes a change in the water content of the skin of the rat within a few hours (16) which is qualitatively comparable to that occurring in the uterus and vagina (16,17).…”
mentioning
confidence: 99%
“…While it is generally recognized that estrogens are without demonstrable effect upon the mean level of arterial blood pressure (8,9,10,11,14,15), evidence is accumulating to show that the effects of estrogen on the peripheral circulation are quite widespread throughout the body, and are of a definite character. The following facts indicate this: the injection of estrogen causes swelling and changes in the water content of the sex-skin in certain primates (12); estrogen causes engorgement of the vessels in the nasal mucosa, including that of women (13); the injection of estrogen in the human is followed by a fall in capillary pressure and dilatation of the nail-bed capillary vessels (14); estrogen causes a decrease of venous pressure in the hand (15); and, finally, estrogen causes a change in the water content of the skin of the rat within a few hours (16) which is qualitatively comparable to that occurring in the uterus and vagina (16,17).…”
mentioning
confidence: 99%
“…Gastrin resists the lipases of plants (166), of the pancreas, and of the liver (167). Laqueur, Hart, and de Jongh (346) confirmed these facts on their watersoluble products, which also showed resistance to pepsin.…”
Section: {E) the Internal Secretion Complex Of The Ovarymentioning
confidence: 70%
“…Doisy, Ralls, Allen, and Johnston (167) reported resistance to saponification by sodium ethylate and this has been confirmed by many workers. Laqueur, Hart, and de Jongh (344) boiled purified preparations with 26 '^^KOH and 26% H2SO4 without causing destruction, and the same authors (346) showed that it resisted 10 ",j KOH up to 170°C. Other THE CESTRUS-PRODUCING HORMONE 91 agents to which it is resistant include NaOH (230), and sodium methylate and butylate (166,167).…”
Section: {E) the Internal Secretion Complex Of The Ovarymentioning
confidence: 99%
See 2 more Smart Citations